2016
DOI: 10.1007/s10964-016-0470-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Psychological Concomitants of Other-Sex Crush Experiences During Early Adolescence

Abstract: Very little empirical attention has been paid to other-sex crush experiences during adolescence. As a result, it is not known whether such experiences, which appear to be relatively common, impact psychological adjustment outcomes. This two-wave (3 month interval) longitudinal study of 268 young adolescents (48% girls; M age at Time 1 = 11.84 years) examined the psychological concomitants of other-sex crush experiences (having and being viewed by others as a crush). Anxious-withdrawal and gender were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…First, we did not measure all possible types of romantic experiences. For example, experiencing crushes 1 and socializing with possible romantic partners 4 are also developmentally salient romantic experiences that were not captured in the 2015 NSSHB. We also did not distinguish between romantic experiences that were online compared with in-person.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, we did not measure all possible types of romantic experiences. For example, experiencing crushes 1 and socializing with possible romantic partners 4 are also developmentally salient romantic experiences that were not captured in the 2015 NSSHB. We also did not distinguish between romantic experiences that were online compared with in-person.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescence marks the emergence of romantic feelings and cognitions 1 that set the stage for participating in romantic activities such as socializing with romantic partners, going on dates, and developing romantic relationships. 2,3 An expansive literature has demonstrated that romantic experiences are associated with multiple domains of adolescent health and well-being.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Crushes are defined as target-specific likings for another person, characterized by one-sided romantic attraction or feelings (Bowker, Spencer, Thomas, & Gyoerkoe, 2012). The current investigation builds on Bowker and colleagues' (Bowker et al, 2012;Bowker & Etkin, 2016) analysis of the developmental significance of other-sex crush experiences among young adolescents in the United States (US). Theory and research findings point to the special…”
mentioning
confidence: 99%